Gynecological surgery caused vesicovaginal fistula managed by Latzko operation - Chi-Yuan Liao; Robert Shan Fon Tasi; Dah-Ching Ding (Elsevier, 2012)
Objective: In developed countries, vesicovaginal fistula (VVF) is a rare complication after gynecological surgery. In this report, the Latzko procedure was used to repair VVF to evaluate its safety and efficacy. Materials and Methods: Between 1991 and 2009, cases in which VVF developed after various gynecological surgeries and repaired using the Latzko procedure were included. The cause of VVF and outcome after Latzko procedure were reported. The previous published reports regarding Latzko procedure were also listed and compared. The median follow-up period was 8 years. Results: Six cases of VVF were documented in this period. All fistulas were simple type with a fistular size of less than 2 cm. In three of six cases, fistulas developed after a hysterectomy for carcinoma in situ of cervix. Of those remaining, one case developed after staging an operation for endometrial adenocarcinoma, while the other two cases occurred after hysterectomy for myoma. Five cases were repaired successfully. One case had postoperative complications such as fever and urinary tract infection. Intraoperative blood loss and hospital stay were minimal. There was no recurrence of VVF postoperatively among successful cases during the follow-up period. Conclusion: Adequate exposure of the fistular site is a key point to a successful repair. The Latzko method is a minimal access procedure for VVF repair. This technique may be considered a first-line treatment of VV fistula.